Clinicopathological Analysis And Mrna Expression Profiling Of G1/S Phase Cyclins And Cdk4 In Formalin Fixed Paraffin Embedded Colorectal Cancer Tissue - Gururuloo, Sarminiyy Lenga (2024)
Introduction: colorectal cancer (crc) is the second most common cancer for both males and females in malaysia. Crc has become a serious health issue as it is mostly diagnosed in the later stage of cancer as well as due to the limitations in current treatment available in the medical industry. Many scientists have proven that crc is caused by the accumulation of certain altered genes over the years and evidence from the literature review reported that cell cycle regulator genes are one of them. However, inadequate research had been carried out on mrna expression studies, especially among the malaysian population. Objectives/hypothesis: the hypothesis for this study is that the mrna expression of cyclins d1, e1, a1, and cdk4 are significantly upregulated in crc tissues in malaysian subjects. Therefore, the objectives of this study are to determine the clinicopathological feature and to evaluate the mrna expression of cyclins d1, e1, a1, and cdk4 of the crc tissues in malaysian subjects, and to understand the correlation between cyclins d1, e1, a1, and cdk4 expressions and their compensatory mechanisms. Methodology: this preliminary study recruited 50 subjects and only 47 of them were histopathologically confirmed sporadic crc patients.